Loretan Litany in the Eastern Christian church practices of the 17th–18th centuries: theological, textological and musicological aspects - Zosim, Olga (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2024)
Relevance of the study. For a long time, the musical tradition of the Uniate Church of the Baroque era, represented, like the Orthodox, by a significant number of partes compositions, was completely unknown not only to the general public, but also to scholars specializing in the ancient sacred music of Eastern Europe. Today, it is important to update the musical heritage of Uniate composers, to emphasize the specific features of their works, namely the combination of church traditions of the Eastern and Western Churches. Particularly promising is the study of genres that were borrowed from Roman Catholic church practice and adapted for the believers of the Uniate Church. In this context, litany is one of the most representative of them, because the practice of reading and singing them during the Baroque era became widespread in Western Europe, and then was quickly adopted by the believers of the Uniate Church. Litany, like a spiritual song of paraliturgical purpose, became a marker of the uniqueness of the Uniate musical tradition and an artistic manifestation of the Basilian Baroque, which has the same cultural-creative potential as the Cossack one. The purpose of the article is to characterize the specifics of the perception of the litany as a liturgical genre in the church practice of the Uniate Church of the Polish-Lithuanian Commonwealth in the 17th — 18th centuries, in particular to reveal the features of the translations of the Latin text of the litany into Church Slavonic and to determine the approaches to its musical interpretation. The methodological basis of the article was the historical cultural, analytical and comparative methods, with the help of which the translations of the Latin text of the Loretan litany into Church Slavonic (with elements of old Ukrainian) of the partes compositions from the Suprasl collection of the late 17th century, the Pochaiv Prayer Book (1793) and the Lemky manuscript songbook (1789 — after 1793) were analyzed, the musical component of the partes litany of Tomasz Szewerowski and an anonymous author was characterized. The results and conclusions. As a result of the Latinization of the Eastern Rite, which began in the 17th century, chants that were not typical of the Eastern Christian church tradition appeared in the liturgical practice of the Uniate Church, among which the Litany to the Mother of God (Loretan) gained particular popularity. The existence of at least two of its translations in Church Slavonic is attested. The first was created in one of the Uniate monastic centers of the Kyiv metropolis at the end of the 17th century, probably in Suprasl, and its textual variants formed the basis for two six-voice partes compositions from the collection of the Suprasl Monastery. The second translation was published in the Pochaiv Prayer Book of 1793, and was later distributed not only through printed publications, but also manuscripts. The texts of the Suprasl and Pochaiv translations differ, sometimes significantly, indicating their autonomy, while both have unchanged translation principles, namely reliance on the Church Slavonic translation of the Holy Scriptures and Eastern Christian hymnography, taking into account, but not blind imitation of the regional Catholic traditions of the Polish-Lithuanian Commonwealth. The music of two partes litanies from the manuscript collection of the Supraśl Monastery reflects current trends in European sacred musical creativity, and also takes into account the experience of writing litanies, which, due to the specificity of the text, required a special approach to the construction of musical dramaturgy. The composers are guided by regional liturgical traditions, as indicated by the texts of the litany translations, and offer their own musical solutions that differ from the Roman Catholic models of that time. Tomasz Szewerowski's litany belongs to the lyrically affected figurative sphere, characteristic of minor works of the Baroque period. It is distinguished by the harmony of form, which is cemented by a musical phraserefrain, which has an additional semantic load (angelic singing) due to the sound of the treble part. In the Litany of the anonymous author, who represents another type of imagery — sublime and solemn, an important role in musical dramaturgy is played by the nature of the musical material and repetition as a means of form-building. A special feature of his litany is an appeal to musical rhetoric, which is generally not characteristic of this genre. In accordance with the liturgical practice of the Uniate Church of the 17th — 18th centuries, partes litanies are appropriately performed accompanied by musical instruments.